'She has like 4000 followers!': the celebrification of self within school social networks. (3rd July 2018) - MacIsaac, Sarah; Kelly, J.; Gray, S.
ABSTRACT: Online social interaction has become integral to contemporary social life, adding new dimensions to how young people learn, interact, and perceive themselves and one another. This paper presents theoretical insights from a year-long ethnographic study within a Scottish secondary school, where participant observation and qualitative interviews were used to explain pupils' informal social relationships. Here, pupils aged 11–18 constructed and negotiated a hyper-surveillanced social space within which many became (or strived to become) visible and 'known' amongst others and where online presentations of self were highly important. This facilitated a celebrity-esque culture amongst the pupil population whereby pupils learnt from and emulated macro celebrity culture and often framed social interactions as entertainment. Central to these practices, was a continual desire to 'make gains in distinction' by demonstrating high social status amongst peers. The paper explores the resulting implications for teaching, learning and pupil wellbeing within contemporary educational environments.